Methodologies of Memory Studies and Sociology of Philosophy in the Study of the History of Philosophy and Science - Olga A. Vlasova (Социологический журнал, 2022)
While interest towards Memory Studies has long been popular when it comes to studying cultural traditions and social groups, the field of science (scientific traditions) describes issues using the traditional language of history, philosophy and sociology of science. This happens despite Memory Studies potentially being a productive asset in this problem field. This paper brings together Memory Studies and R. Collins’ sociology of philosophy, while presenting a new strategy for problematization based on the history of philosophy. Memory Studies and sociology of philosophies are presented as two complementary approaches that have interdisciplinary prospects for understanding the methodological problems of the humanities in general and philosophy in particular. The foundations of the approaches are analyzed, a comparative analysis is conducted of the conceptual apparatus, examples of explication of sociological tools in the field of current philosophical discussions are considered. How does philosophy work with the past, how does the “past-present” dialectic unfold in the community of philosophers, how do mnemonic practices determine the lines of power in this field? How are “sacred texts” selected in academic communities, what role do mnemonic practices play when it comes to generational bonds? What sort of practices circulate in the community in terms of condemning or accepting figures from the past? All of these issues are analyzed in the study, based on the concepts of Memory Studies and sociology of philosophy while invoking the ideas of R. Collins’ critics, as well as methodological historical and philosophical works. The approach offered by the author makes it possible to expand Memory Studies and sociology of philosophy into the field of history of philosophy and lay the foundations for such studies in the history, sociology and philosophy of science.